Decoupling of degradation from deadenylation reshapes poly(A) tail length in yeast meiosis - Wiener, David; Antebi, Yaron; Schwartz, Schraga (Nature structural & molecular biology, 2021)
Nascent messenger RNA is endowed with a poly(A) tail that is subject to gradual deadenylation and subsequent degradation in the cytoplasm. Deadenylation and degradation rates are typically correlated, rendering it difficult to dissect the determinants governing each of these processes and the mechanistic basis of their coupling. Here we developed an approach that allows systematic, robust and multiplexed quantification of poly(A) tails in Saccharomyces cerevisiae . Our results suggest that mRNA deadenylation and degradation rates are decoupled during meiosis, and that transcript length is a major determinant of deadenylation rates and a key contributor to reshaping of poly(A) tail lengths. Meiosis-specific decoupling also leads to unique positive associations between poly(A) tail length and gene expression. The decoupling is associated with a focal localization pattern of the RNA degradation factor Xrn1, and can be phenocopied by Xrn1 deletion under nonmeiotic conditions. Importantly, the association of transcript length with deadenylation rates is conserved across eukaryotes. Our study uncovers a factor that shapes deadenylation rate and reveals a unique context in which degradation is decoupled from deadenylation. The discovery that mRNA degradation and deadenylation are uncoupled during meiosis in budding yeast provides a unique context to examine the regulation of each process individually, and reveals that transcript length is a determinant of deadenylation rates across eukaryotes.